(untitled) (Reflection and Critique Law Magazine, 2026)
The study aimed to analytically develop the role of constitutional courts and militant democracy—a concept developed by Karl Loewenstein—as instruments for protecting the Rule of Law in the face of numerous populist and authoritarian threats observed throughout history. The temporal context, particularly in Latin America, underscored the notion that the institutional role, here embodied by constitutional courts, if ineffective, will lead to irreparable consequences for a nation’s identity. The relevance of the research is justified by the intensification, in various contexts, of practices aimed at weakening democratic institutions, making it necessary to reflect on legal and civil mechanisms of containment. The approach adopted was theoretical, based on a literature review of authors such as Loewenstein, Voßkuhle, and Weffort—scholars of the subject—combined with a case study of the attacks that took place on January 8, 2023, in Brazil. On this occasion, supporters of former President Jair Bolsonaro invaded the headquarters of democratic institutions, employing populist tactics to delegitimize the electoral process in an attempt to seize power—an act of violence against democracy. In the following chapters, the complementarity of classical concepts with contemporary narratives emerged organically, allowing for an understanding of the need to revisit the past in order to defend the present. The findings indicated that constitutional courts serve as a legitimate instrument for ensuring that state actions conform to the Constitution, while militant democracy, by immunizing itself, criminalized anti-democratic behavior, establishing a dual protection system. This essay also highlights a notable paradox: authoritarian containment measures, if poorly calibrated, can undermine democratic freedoms. Therefore, the conclusion proposed is that institutional strengthening and civic education are essential elements for a sustainable defense against populism.